Evaluation of the suitability of introduction of multifunctional samples of aviation ground equipment in aircraft maintenance - Bilyakovych, O.N.; Savchuk, A.N.; Turitsa, Y.A.; Kurbet, L.V. (Problems of Tribology, 2021)
Quite often there is an oversaturation of the platform with ground aircraft, which is designed for the operation of modern international airports, especially in the so-called "rush hour". The emergence of such a situation may affect the emergence of risks in the implementation of airport technologies, which are associated with a probable reduction in the level of safety of ground vehicles on the platform, the formation of clusters of aircraft maintenance at the parking lot and the possibility of damage to aircraft on the ground, psychological stress aviation personnel and other unforeseen situations. To avoid melon situations that are directly related to the possible danger at airports, it is necessary to use multifunctional models of aviation ground equipment, which will provide several technological processes for ground handling of aircraft, passengers, mail and cargo by creating hybrid structures of special vehicles and equipment. and automation. For example, the use of multifunctional telescopic ladders allows not only to ensure a high level of comfort when boarding / disembarking passengers in aircraft, but also significantly increase the parking space in the buffer area of ​​ground maintenance of aircraft for other types of ground aircraft by reducing the latter, which will increase the level of safety of aircraft maintenance and economic efficiency in the activities of airport services and handling companies.